The effect of parallel projection towards image performance - Mohd. Muji, Siti Zarina (2011)
In tomography, there are two common projection namely, parallel beam and fan beam. Both projections give a different impact towards system performance and the image itself. This paper will focus on the attenuation factor that affects towards images in parallel projection. The focuses are to see the differences between one, two, three and four projections towards image performance. The projection is come from light that is produced by LED infrared while photodiode is act as receiver. Any appearance of object between transmitter and receiver will change the voltage that is produce by receiver. The bigger the object, the more voltage losses will be sensed. The voltage loss will be manipulated to form an image where it is found out that the more the projection is applied, the image will be displayed clearer and have more information on it.